The Relationship between Completeness of Medical Information and the Accuracy of Diagnosis Codes for BPJS Inpatients at Hospital X Malang City : Hubungan Kelengkapan Informasi Medis Terhadap Keakuratan Kode Diagnosis Pasien BPJS Rawat Inap RS X Kota Malang - Annisa, Nadia Salma; Akbar, Prima Soultoni (Universitas Muhammadiyah Sidaorjo, 2025)
Background: Completeness of medical information is critical in ensuring diagnosis code accuracy. The purpose of this study is to look at the relationship between medical information completeness and diagnosis code correctness in BPJS Patient Inpatient Medical Record Documents. Subjects and Methods: This form of research employs both quantitative and correlational methodologies. The sample consisted of 83 documents chosen at random. Chi-square was employed to analyse the data. Results: The ratio of complete medical information is 60%, whereas incomplete medical information is 40%. Medical resumes with 19 papers had the highest percentage of incompleteness (23%). The accuracy of hospital record diagnostic codes is 40%, while inaccuracies are 60%. Inaccuracies in diagnosis codes are generated by a variety of circumstances, including wrongly defining the major diagnosis, officers being less cautious, and providing inadequate support. The chi square statistical test results in p = 0.0019. Conclusion: there is a correlation between the completeness of medical information and the accuracy of diagnosis codes in BPJS patient inpatient records. The author recommends that health professionals be more attentive when entering medical information, coders follow fundamental ICD 10 rules, and institutions provide coder training to ensure that coding activities operate smoothly.